The concept of state recognition and legislative recognition of the social rights of the individual categories, classes and groups in the second half of the XIX – early XX century: historical and legal aspect - Походзіло, Ю. М. (Theory and practice of jurisprudence, 2016)
Problem setting: Analyzed some aspects of public recognition and the law on social rights of certain groups, classes and groups in the second half of XIX − early XX century and progressive ideas and international legal principles of social rights. Recent research and publications analysis: The concept of public recognition and the law on social rights of certain groups, classes and groups in the second half of XIX − early XX century is considered a scientific heritage Shelhamina I. I., Kalensky V. G., Holdenvyeyzera A. A., Smirnovа А. F., Vyhdorchyka N. A. et al. Paper objective: The development of human rights in the second half of XIX − early XX century and securing new kind of rights − social. Paper main body: Analysis of the historical development of public charity and social rights and their protection. Conclusions of the research: In the proposed period of social legislation, developing, was fragmented and does not have a comprehensive social protection, but was recognized by society and the State and provided appropriate mechanisms. 2 Basic annotation to the article: The article is devoted to particular aspects of public recognition and the law on social rights of certain groups, classes and groups in the second half of XIX − early XX century. The article analyzes the progressive ideas and international legal principles of social rights. It is concluded that the development of social legislation in the second half of XIX − the beginning of the twentieth century was due to the social needs of the most massive part of the population of this period − the working class. These rights were fragmentary and did not have a comprehensive social protection, they were recognized by society and the state, as well as were provided with appropriate means of implementation.